Paraedessa, a new genus of Edessinae (Hemiptera: Heteroptera: Pentatomidae) - Da Silva, Valéria Juliete; Nunes, Benedito Mendes; Fernandes, José Antônio Marin (Zootaxa, 2013)
The new genus Paraedessa is proposed, to include four species previously placed in Edessa. The new genus is characterized by males with the pygophore showing a lateral expansion of proctiger, and females with gonocoxites 8 reduced; gonapophyses 8 exposed and sclerotized. The species are very similar and their identification is possible only by comparing genitalia. New combinations proposed are Paraedessa stolida (Linnaeus) from Suriname and Brazil; P. heymonsi (Breddin) from Peru and Bolivia; P. verhoeffi (Breddin) from Venezuela, Colombia, Peru and Brazil and P. paravinula (Barber) from Puerto Rico. New species proposed are P. albomaculata from Suriname; P. cyanodorsata from Costa Rica, Panama and Venezuela; P. ecuadoriensis from Colombia and Ecuador; P. silvicola from French Guiana; P. subretangulata from Nicaragua, Costa Rica, Colombia and Venezuela. The species were illustrated and photographed. Descriptions were made using mostly male and female genitalia external morphological characters. A key and distribution map for the species are also provided.